Value experiential learning pada kisah Nabi Ibrahim a.s. dan Nabi Ismail a.s. dalam surat al-Shaffat ayat 100-111 - Saipon, Abdul; Sumantri (Tawazun: Jurnal Pendidikan Islam, 2023)
Experience-based learning in educational research studies has proven to be effective in improving students’ academic performance. Therefore, it is necessary to study whether there may be verses in the Koran that are relevant to this. This research aims to analyze the value of experience-based learning that occurs in the story of Prophet Ibrahim AS and Prophet Ismail as contained in Q.S Al-Saffat: 100-111. A qualitative approach to library research is used to obtain appropriate research results. The literature reviewed in this research is the Al-Qur’an and tafsir books as primary data sources and journal articles and books as secondary data sources. Meanwhile, the method of interpretation used is the Maudhu’i interpretation method, namely by examining the verses from various aspects, and carrying out analysis based on correct knowledge which is used to explain the main problem, so that you can understand the problems and meaning of the verses easily. The sources that the researchers used were the Jalaludin Asy-Syuyuthi and Jalaludin Muhammad Ibn Ahmad Al-Mahali’s commentary on Jalalain, the Ibn Katsir commentary by Imaduddin Abul Fida’ Isma’il bin ’Umar bin Katsir and the al-Misbah commentary by Muhammad Qurais Shihab. The Value of Experiential learning in the Story of Prophet Ibrahim a.s and Prophet Ismail a.s in Surah Al-Shaffat Verses 100-111 is: One, Aqidah education about faith. This Aqidah education. The order to slaughter Ibrahim is closely related to Ismail’s right to life. Carrying out these orders does not only involve mental and emotional readiness, but you must also have high spirituality, in other words, have mature faith. Two, moral education. Moral education can be achieved by being patient and obedient to parents. Abstrak Pembelajaran berbasis pengalaman dalam kajian penelitian pendidikan terbukti efektif dalam meningkatkan performa akademik peserta didik. Oleh karena itu perlu dikaji apakah mungkin ada ayat dalam Al-Quran yang relevan dengan ini. Penelitian ini bertujuan untuk menganalisis nilai pembelajaran berbasis pengalaman yang terjadi dalam kisah Nabi Ibrahim AS dan Nabi Ismail yang termaktub dalam Q.S Al-Shaffat: 100-111. Pendekatan kualitatif studi kepustakaan (library research) digunakan untuk memperoleh hasil penelitian yang sesuai. Literatur yang ditelaah dalam penelitian ini berupa al-Qur’an dan kitab-kitab tafsir sebagai sumber data primer serta artikel jurnal dan buku sebagai sumber data sekunder. Sementara metode tafsir yang digunakan yaitu metode tafsir maudhu’i yaitu dengan cara meneliti ayat-ayat dari berbagai segi, dan melakukan analisis berdasarkan ilmu yang benar yang digunakan untuk menjelaskan pokok permasalahan, sehingga dapat memahami permasalahan dan maksud ayat-ayat tersebut dengan mudah. Adapun sumber yang peneliti pakai adalah tafsir Jalalain karangan Jalaludin Asy-Syuyuthi dan Jalaludin Muhammad Ibn Ahmad Al-Mahali, tafsir Ibnu Katsir karangan Imaduddin Abul Fida’ Isma’il bin ‘Umar bin Katsir dan tafsir al-Misbah karangan Muhammad Qurais Shihab. Adapun Value Experiential learning pada kisah nabi Ibrahim a.s. dan Nabi Ismail a.s. dalam surat Al-Shaffat Ayat 100-111 yaitu: Satu, pendidikan Aqidah tentang keimanan. Pendidikan Aqidah ini Perintah penyembelihan pada Ibrahim sangat berhubungan dalam hak hidup Ismail. Dalam melaksanakan perintah tersebut tidak hanya melibatkan kesiapan mental dan emosional saja, melainkan juga harus mempunyai spiritualitas yang tinggi, dengan kata lain mempunyai keimanan yang matang. Dua, pendidikan akhlak. Pendidikan akhlak dapat ditempuh dengan sabar dan taat kepada orang tua. Kata Kunci. Nilai pembelajaran berbasis pengalaman; Nabi Ibrahim; Nabi Ismail; Surat Al-Shaffat ayat 100-111.